Valdosta High School Scrapbook 5, September – November 1962 - Valdosta High School (My University, 1962)
This item contains newspaper clippings and photographs. This primarily focuses on the sports teams for Valdosta High School.
This item contains 1 PDF File with 93 pages and a title page
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.)